Hubungan Pengetahuan dan Tingkat Kepatuhan terhadap Penggunaan Masker pada Masa Pandemi Covid-19 di RSPAD Gatot Soebroto Tahun 2020 - Leni Suhartini (Maternal & Neonatal Health Journal, 2021)
Casualties due to Covid-19 are increasing every day. The disease attacks the respiratory tract and transmitted through droplets when the sufferer speaks, coughs or sneezes. In some people do not cause symptoms, but in some patients there are also those that cause symptoms from mild to severe. Wearing a mask is one of the efforts made to prevent and protect from contaminated viruses. Objective: to assess the relationship of knowledge and the level of compliance with the use of masks during the Covid-19 pandemic.  Research methods. Mused cross sectional method, sampled 32 respondents (consisting of 16 maternity room midwives and 16 final-level students). The data used is primary data collected using research instruments in the form of questionnaires distributed through google form. Analisys using Chi Square with tools of SPSS application. Result.  In terms of knowledge obtained results in midwives good knowledge as many as 13 people (81,3%) and less knowledge of 3 people (18,8%). In good knowledge students as many as 10 people (62,5%) and less knowledge of 6 people (37,5%) P value = 0,432 and OR 0,385. From the level of compliance, midwives who do not comply with the use of masks as many as 5 people (31,3%) and who obeyed as many as 11 people (68,8%). Midwives students all are disobedient to the use of masks.  Statistical test results obtained the value p = 0,001 OR = 0,313. Conclusion. The use of masks is part of a comprehensive series of measures to prevent and control the spread of Covid-19 disease. High knowledge is not necessarily obedient to the use of masks, it is necessary awareness of each individual to use the mask according to the situation and conditions.